Biofilms in water, its role and impact in human disease transmission - Huq, Anwar; Whitehouse, Chris A.; Grim, Christopher J.; Alam, Munirul; Rita R. Colwell (Current Opinion in BiotechnologyCurrent Opinion in Biotechnology, 2008)
Understanding the mechanism of biofilm formation is the first step in determining its function and, thereby, its impact and role in the environment. Extensive studies accomplished during the past few years have elucidated the genetics and biochemistry of biofilm formation. Cell-to-cell communication, that is, quorum sensing, is a key factor in the initiation of biofilm. Occurrence of viable but nonculturable bacteria, including Vibrio cholerae in biofilms has been reported and most likely such cells were overlooked previously because appropriate methods of detection were not employed. For this reason discovery and investigation of this important bacterial ecological niche in the environment were impeded.